Identification of Leading Sector Priorities and Spatial Interactions as Effort to Increase The Economic Growth Rate of Bondowoso District - Mariya Ulfa; Ahmad Fauzi; Moh. Rofiqi Hidayat (East Java Economic Journal, 2020)
Bondowoso Regency is one of the regions categorized as underdeveloped because the average value of growth rate during 2010-2019 is below the average value of the growth rate of East Java Province which is 5.38% while the East Java Province reaches 5.82%. In addition, the GDP value of Bondowoso regency is in the 8th lowest rank of all regencies / cities in East Java and ranks 2nd in the area of Besuki residence. The economic structure of Bondowoso Regency is dominated by the primary sector with a contribution of 37.4%. As a region that has a strategic area, sectoral development planning is needed by setting sector priorities that must be developed based on competitive advantage and industrial competitiveness and determination of spatial interaction. This research is a type of descriptive quantitative research with the data used are secondary time-series data from 2010-2019. Data taken from Bondowoso’s Cental of Statictis Institution and East Java’s Cental of Statictis Institution. To meet the research objectives there are several analytical tools used including LQ, DLQ, Shift-Share, Growth Ratio Model. Overlay Analysis, Sectoral Typology, Gravitation Model, Spider Chart analysis, and Williamosn Index. Based on the use of a combination of LQ, MPR, Overlay, Sectoral Typology it is known that there are 7 leading sectors namely agriculture, forestry and fisheries; government administration, defense and mandatory social security sectors; education service sector; other service sectors; health service sector and social activities; information and communication sector; financial services and insurance sector. Based on the combination of the Shift Share, DLQ, MPR, Overlay and Sectoral Typology analysis tools, it is known that there are sectors that are expected to become leading sectors in the short, medium and long term. The result shows that Bondowoso district has highest interaction value than other district and disparities value of Bondowoso is classified in low disparity.